2013
DOI: 10.1021/es400966x
|View full text |Cite
|
Sign up to set email alerts
|

CO2Capture from Simulated Fuel Gas Mixtures Using Semiclathrate Hydrates Formed by Quaternary Ammonium Salts

Abstract: In order to investigate the feasibility of semiclathrate hydrate-based precombustion CO2 capture, thermodynamic, kinetic, and spectroscopic studies were undertaken on the semiclathrate hydrates formed from a fuel gas mixture of H2 (60%) + CO2 (40%) in the presence of quaternary ammonium salts (QASs) such as tetra-n-butylammonium bromide (TBAB) and fluoride (TBAF). The inclusion of QASs demonstrated significantly stabilized hydrate dissociation conditions. This effect was greater for TBAF than TBAB. However, du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
101
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(102 citation statements)
references
References 41 publications
1
101
0
Order By: Relevance
“…Gas hydrates have been utilized in various fields: from exploitation of naturally occurring gas hydrates, natural gas storage and transportation, carbon dioxide capture and sequestration, to desalination [3][4][5][6][7][8][9][10]. Among their various applications, hydrate-based desalination has recently attracted significant attention because the need for desalination is increasing due to water shortages and the sources for desalination are not limited to seawater.…”
Section: Introductionmentioning
confidence: 99%
“…Gas hydrates have been utilized in various fields: from exploitation of naturally occurring gas hydrates, natural gas storage and transportation, carbon dioxide capture and sequestration, to desalination [3][4][5][6][7][8][9][10]. Among their various applications, hydrate-based desalination has recently attracted significant attention because the need for desalination is increasing due to water shortages and the sources for desalination are not limited to seawater.…”
Section: Introductionmentioning
confidence: 99%
“…While in the case of the simulated biogas mixture hydrate formed with TBAB-DMSO, the peak at 1286 cm À1 was observed shift to 1278 cm À1 except that the peak at 1381 cm À1 was the same position as that of the THF-DMSO case. It is well known that Raman peaks at 1278 cm À1 and 1381 cm À1 should correspond to CO 2 occupies both 5 12 6 2 and 5 12 6 3 cages of the semiclathrate hydrate framework [14,49,51]. It should be noted that the relative intensity of peak splitting at 1307 cm À1 and 1326 cm À1 are likely corresponding to a change in the structural environment of the alkyl groups and can be attributed to CH 2 -bending modes in this spectral region [52].…”
Section: Resultsmentioning
confidence: 91%
“…Quaternary ammonium salts, such as Bu4NBr, Et4NBr, are currently in use for industrial preparation of cyclic carbonates [50], and therefore have attracted much scientific attention in the development of heterogeneous catalysts for these applications. Recent studies also revealed the use semi-clathrate hydrates in the presence of quaternary ammonia salts of TBAB for CO2 capture up to 95% [51,52].…”
Section: Nonmetal Catalysts Quaternized Chitosanmentioning
confidence: 99%